The bionic blues: Robot rejection lowers self-esteem. (January 2018) - Nash, Kyle; Lea, Johanna M.; Davies, Thomas; Yogeeswaran, Kumar
Abstract: Humans can fulfill their social needs with fictional and non-living entities that act as social surrogates. Though recent research demonstrates that social surrogates have beneficial effects on the individual similar to human relations, it is unclear whether surrogates can also cause similar harm to humans through social rejection. After playing a game of connect-4 with a human-sized robot, participants were informed by the robot that it would like to see them again (acceptance), would not like to see them again (rejection), or told nothing regarding a future interaction (control). Data revealed that social rejection from a robot significantly reduced self-esteem relative to receiving no-feedback and social acceptance (the latter two did not differ from each other). However, robot rejection had no impact on negative attitudes and opposition to the use of robots in everyday life. These findings demonstrate that social surrogates have the potential to cause psychological harm. Highlights: Examines influence of robot rejection and acceptance on human self-esteem. Robot rejection decreased self-esteem, while acceptance had no effect on self-esteem. Demonstrates that robot rejection can cause psychological harm.